Influence of human resources and organizational culture on the satisfaction of the service of Sapta Marga Village Pelambik Praya Village Southwest Pelambik Praya Regency - Sami’un, Sami’un; Amirullah, Ahmad Fatoni Karim; Wijaya, I Ketut Kusuma (Law and Economics, 2025)
This study aims to analyze the influence of the quality of human resources (HR), organizational culture, and Sapta Marga values on community satisfaction in public services in Pelambik Village, Southwest Praya District, Central Lombok Regency. A quantitative approach with a survey method was used, involving 95 respondents selected through proportional random sampling. Data were collected using Likert scale questionnaires, structured interviews, and documentation, then analyzed by multiple linear regression. The results of the study show that the quality of human resources, organizational culture, and values of Sapta Marga have a positive and significant influence on community satisfaction, both partially and simultaneously. The value of Sapta Marga has the most dominant influence, followed by the quality of human resources and organizational culture. The determination coefficient (R²) test showed that 72.1% of the variation in community satisfaction could be explained by these three variables, while the rest was influenced by other factors such as infrastructure, regulations, and community participation. These findings confirm that improving the quality of public services at the village level requires synergy between improving the competence of the apparatus, fostering a positive organizational culture, and internalizing moral values such as Sapta Marga. This integrated strategy can strengthen the professionalism of the apparatus, increase the humanist service orientation, and strengthen the community's legitimacy and trust in the village government.